Practical use of immobilized lysozyme for the remediation process of Escherichia coli in aqueous solution - Alves, Carlucio R.; Pimenta, Maria Gardenny R.; Vieira, Regine H.S.F.; Furtado, Roselayne F.; Guedes, Maria Izabel F.; Silva, Rui C.B.; Assis, Odilio B.G. (Electronic Journal of Biotechnology, 2007)
The lysozyme enzyme was immobilized on vitreous surface (fragments with diameters of 0.3 and 1.0 mm) for remediation of the microorganism Escherichia coli JM 109 into fresh water and saline solutions with 0.9% NaCl (w/v). Characterization of enzymatic film was carried out by infrared spectroscopy and atomic force microscopy techniques. Bactericide activity of the enzyme was evaluated by spectrophotometric analysis. It was verified that the enzymatic film was strongly coupled with the vitreous surface. The topographic analysis demonstrated that the deposited film was uniform and homogeneous. It was observed bactericide activity of film deposited on vitreous surface with 0.3 mm in fresh and saline solutions. This fact was not verified to vitreous fragments with 1.0 mm of diameter.